ENVIRONMENTAL POLLUTION - HUMAN HEALTH (A WORLDWIDE PROBLEM): पर्यावरणप्रदूषण-मानवस्वास्थ्य (एक विश्वव्यापी समस्या) - Joshi, Tripti (International Journal of Research -GRANTHAALAYAH, 2015)
Modern development has caused a lot of people attention about the deadly aspects of the industrial revolution, due to the fact that there is a lot of industrial corruption. आधुनिकविकासकाप्रतीकबनकरआईऔद्योगिकक्रांतिके घातकपहलुओं के बारेमेंबहुत कम लोगोंका ध्यानजापायाहैजानेकितनेलोगऔद्योगिकप्रदुषण के कारणतिल-तिलकरमरतेहैं।दिनांदिनप्रदुषितहोतेपर्यावरण के कारणसंक्रामकबीमारियाँ न सिर्फभारतमेंअपितुविश्व के अधिकांशदेशोंमें बढ़तीजारहीहै।भारतहीनहींसम्पणर््ूाविश्वमेंबीमारियोंका खतराहरदिन बढ़ रहाहै।